Tindak Tutur Ilokusi Dalam Series Kalau Jodoh Takkan Kemana Season 2 di Youtube Indosat Ooredoo Hutchison - Nurkhofifah, Nanda (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research aims to find out and describe the form of illocutionary speech acts in the series “If Your Soulmate Will Not Go Where” Season 2 in episode 1 on the Indosat Ooredoo Hutchison Youtube channel. The research method used in this research is a qualitative descriptive method. Research data was analyzed using skillful free-involved listening and note-taking techniques. The total research analysis data amounted to 15 data, namely assertive (declaring) illocutionary speech acts with 4 data, directives (ordering 1 data, commanding 2 data, begging 1 data, advising 1 data), expressive (apologizing 1 data, blaming 1 data, praising 3 data), and commissive (offering something) with 1 data.